Paradoxical pustular psoriasis in a patient with spondyloarthritis treated with secukinumab - Daniela Anghel; Mihaela Georgescu; Marcela Poenaru; Diana Maria Orleanu; George Sorin Tiplica (Wiley, 2023)
Abstract Secukinumab is a monoclonal antibody used to specifically inhibit pathologic interleukin‐17 and therefore effectively manage conditions like plaque psoriasis, psoriatic arthritis and ankylosing spondylitis. Although we know that antitumor necrosis factor molecules can cause paradoxical pustular psoriasis, a few case reports noted this reaction in patients treated with secukinumab. We report a case of a paradoxical drug reaction consisting of palmar pustular psoriasis in a female patient treated with secukinumab for spondyloarthritis.